Causes of upper gastrointestinal bleeding in patients admitted to Erbil hospitals - Halgurd Fathulla Ahmed (Advanced Medical Journal)
Background and objectives: This study aimed to Find the causes of upper gastrointestinal bleeding in Erbil hospitals and to study these causes for the purpose of reducing their mortality.